Leadership Practices and Talent Turnover: Study on Yemeni Organizations - Rajiani, Ismi (Sciedu Press, 2013)
To date, many studies have been conducted in order to identify factors that have a great impact on employees’ turnover. A number of studies have shown that leadership style influences employees’ job satisfaction and their turnover intention. However, very few studies have dealt with the relationship between Kouzes and Posner (1987)’s leadership practices and employees’ turnover. This study aims to identify the role that Leadership practices play in enhancing loyalty and at the same time reducing turnover intention among the most valuable employees - talent employees - in telecommunication sector in Yemen. In addition, current study also aims at examine whether the relationship between leadership practices and turnover intention is mediated by the talent employees’ job satisfaction. Using the response of 280 employees working in the five Yemeni telecommunication organizations, the results indicated that there is a negative relationship between overall leadership practices and turnover intentions among talent employees, four out of five practices were negatively correlated with talent employees’ turnover intention. Moreover, job satisfaction founded to be a mediator of the relationship between leadership practices and turnover intentions.